Protected steel columns vs partially encased columns: Fire resistance and economic considerations. (September 2016) - Piquer, A.; Hernández-Figueirido, D.
Abstract: As is commonly known, resistant properties of steel columns decrease quickly with an increase in temperature. Thus, steel columns are usually surrounded with low thermal conductivity materials that protect them at high temperatures. Another interesting alternative is the use of partially encased columns, a sort of steel-concrete composite column. Focused on fire performance and economic cost of a standard column, this paper presents a comparison study between partially encased composite columns and I-shaped steel columns with and without protection. A range of geometric cross-sections and material properties have been tested and the Pareto frontier has been used to show the cheapest columns with the best performance. The study is carried out assuming geometrical and material restrictions accepted by the European codes and imposing a constant axial load. Results show that most of studied protected columns resist around 120 min before collapsing in fire conditions. The structural response of partially encased composite (PEC) columns under simulated fire conditions is good and it can be seen from this study that significant savings can be obtained with a good design of PEC column, savings around 50%. The relative costs of the three design options studied are quantified. Considerations about the geometry and materials criteria are provided. All steel sections described in this study are commercial ones, which includes European, British, American, Japanese and Russian standard steel sections. Highlights: Comparison study between partially encased composite (PEC) columns and I-shaped steel columns with and without protection Economic cost and fire performance comparison Significant savings can be obtained with a good design of PEC column. The most economical PEC columns are built with low steel yield limit and high strength concrete.